Penggunaan E-Modul Berbasis Aplikasi Heyzine Flipbook untuk Mengembangkan Kemampuan Historical Literacy dalam Pembelajaran Sejarah Abad XXI - Sekar Ayu Febriantie; Wawan Darmawan; Yeni Kurniawati Sumantri (Universitas Hamzanwadi, 2024)
Understanding history is more complex than just understanding past events. One way that can be done to foster an understanding of history is by developing historical literacy skills. Students' historical literacy skills can be strengthened by utilizing applications in the history learning process integrated with digital technology. This study aims to explain the utilization or potential of electronic modules based on the heyzine flipbook application in developing students' historical literacy skills in history learning. By using the integrative review type literature review method, researchers describe the use of electronic modules based on the heyzine flipbook application through a number of features contained in the application, which consist of link features, videos, images, audio, and so on. In the heyzine flipbook application, there are various features that make it easy for users to develop interactive teaching materials. These features are in the interactions column which focuses on editing the module to be created. The features are link, image, video, audio and web features. Through this article, the researcher aims to provide a solution for utilizing electronic modules based on the heyzine flipbook application as one of the media that can be utilized in the history learning process so that history is not considered a field of study that emphasizes the memorization process alone and is able to develop students' historical literacy skills.